Association Between Religiosity and Spirituality and Cocaine Use: A Systematic Review - Buja, Alessandra (Journal of religion and health, 2024)
Previous literature has evidenced a possible impact on health, mental health, and health-related faith behaviors due to the effects of an individual’s spiritual dimension. The aim of this study is to collect and summarize all current data from observational studies regarding the association between religiosity or spirituality (R/S) and cocaine use (CU). A systematic literature search of analytical observational studies on the association between religiosity or spirituality and the use of cocaine was performed in PubMed and Scopus databases. Twenty observational studies were included in this review. Fifteen of the twenty observational studies found that a higher level of religiosity was associated with lower lifetime and actual cocaine use, both in adults and adolescents. However, one study conducted in a sexual minorities sample found that higher religiosity—measured as frequency of private religious activities such as prayer—was associated with a higher probability of cocaine use. Two studies found no evidence of any association between religiosity and cocaine use, and two found mixed results. This review found a possible protective role of religiosity on cocaine use, even if the cross-sectional nature of the greater part of the studies prevented drawing any casual relation. Future studies with a longitudinal approach are required. However, the support of activities aimed at broadening a religious attitude and beliefs could result in creating an environment protective for young people against cocaine use.